A hybrid multi-objective GRASP+SA algorithm with incorporation of preferences - Oliveira, Eunice; Henggeler Antunes, Carlos; Gomes, Alvaro (2014 IEEE Symposium on Computational Intelligence in Multi-Criteria Decision-Making (MCDM), 2014)
A hybrid multi-objective approach based on GRASP (Greedy Randomized Adaptive Search Procedure) and SA (Simulated Annealing) meta-heuristics is proposed to provide decision support in a direct load control problem in electricity distribution networks. The main contributions of this paper are new techniques for the incorporation of preferences in these meta-heuristics and their hybridization. Preferences are included in the construction phase of multi-objective GRASP, in SA, as well as in the selection of solutions that go to the next generation, with the aim to obtain solutions more in accordance with the preferences elicited from a decision maker. The incorporation of preferences is made operational using the principles of the ELECTRE TRI method, which is based on the exploitation of an outranking relation in the framework of the sorting problem.